Nonlinear dynamics of a vibro-impact system subjected to electromagnetic interactions - Jong, Si-Chung (2015)
Impact moling is an effective method of pile driving and percussive drilling to bore underground tunnel for various civil applications such as pipe, cable and ducts installation.